A meta‐analysis of the effectiveness and safety of kinesiology taping in the management of cancer‐related lymphoedema. (11th May 2016) - Gatt, M.; Willis, S.; Leuschner, S.
Abstract : Patients with cancer‐related lymphoedema (CRL) commonly refuse treatment with bandaging or hosiery because of hot and humid weather conditions. This review aims to determine the effectiveness and safety of kinesiotaping (KT) in the management of CRL compared to compression bandaging or hosiery. A systematic search of the literature was conducted until July 2015. The primary outcomes were reduction in body part volume or circumference and adverse effects of the interventions. The secondary outcomes were subjective experience of the treatment, severity of lymphoedema‐related symptoms and patients' quality of life (QoL). Six randomised controlled trials (RCTs) were included in this review. Five were included in the meta‐analysis of the primary outcome limb volume ( n  = 203, KT n  = 91, compression n  = 112). It revealed no significant difference between the interventions [WMD −205.33 mL CI (−454.69 to 44.04) P  = 0.11]. An increased risk of skin complications with KT was reported in five studies affecting between 10% and 21% of patients. Where lymphoedema‐related symptoms were reported KT was found to be superior to compression. Paradoxically, patients receiving bandaging reported a higher QoL. KT was not found to be more comfortable than bandaging. KT should only be used with great caution where bandaging cannot be used.